Evaluation of Mechanical and Physical Properties of Clinically Used and Recycled Superelastic NiTi Wires - Venkata Naidu Bavikati; Gowri Sankar Singa Raju; Prasad Mandava; Sai Sandeep Killamsetty; Venkates Enkatesh Nettamettam; Praveenaveen Kumar Reddy Karnatinati (Journal of Clinical and Diagnostic Research, 2016)
Introduction: The initial leveling and aligning phase has been simplified with the introduction of superelastic nickel-titanium archwires. The relatively high cost of these wires has prompted some of the clinicians to reuse them after sterilization. The quantitative changes in the surface properties of superelastic ‘NiTi’ wires after clinical application and recycling by autoclave method have not been established in earlier studies. Aim: To quantify the changes in mechanical and physical properties of four different commercially available superelastic nitinol (NiTi) archwires after clinical usage and recycling. Materials and Methods: The superelastic ‘NiTi archwires obtained from four different manufacturers: Group I-GAC (McMinnville, USA); Group II- 3M Company (California, USA); Group III- G&H Company(Franklin, USA) and Group IV- American Orthodontics (AO) (Sheboygan, USA) were selected for the study. Each of the four groups comprised of 20 samples of wire with 10 of them selected randomly as control and remaining 10 as test specimen in each group. The experimental archwires were placed on selected patients for a period of three months followed by Standard Autoclave sterilization at 121°C and 15 to 20 psi pressure for 20 minutes and were retrieved. The tensile strength was evaluated by Instron-Universal Testing Machine. The quantification of changes in surface roughness was investigated by grid method using Scanning Electron Microscope (SEM). The Control Wires (C) were evaluated at initial time “T1” where as the Experimental sample of wires (T) were subjected to testing at an initial time ‘T1’ and after clinical usage and sterilization at ‘T2’ Statistical Analysis: Paired t-test was used for intra-group comparison and one way ANOVA and Post Hoc Tukey tests were used for inter-group comparison. Results: There was significant decrease in tensile strength (p = 0.0015 to 0.001) and surface roughness (p< 0.001) between control and experimental arch wires within each group when properties at T1 and T2 were compared. Conclusion: The study suggests discouraging the use of clinically used and sterilized superelastic NiTi archwires.